Normalization of Blood Pressure With Spinal Cord Epidural Stimulation After Severe Spinal Cord Injury - Harkema, Susan J.; Wang, Siqi; Angeli, Claudia A.; Chen, Yangsheng; Boakye, Maxwell; Ugiliweneza, Beatrice; Hirsch, Glenn A. (Frontiers in Human Neuroscience, 2018)
Chronic low blood pressure and orthostatic hypotension remain challenging clinical issues after severe spinal cord injury (SCI), affecting health, rehabilitation and quality of life. We previously reported that targeted lumbosacral spinal cord epidural stimulation (scES) could promote stand and step functions and restore voluntary movement in patients with chronic motor complete SCI. This study addresses the effects of targeted scES for cardiovascular function (CV-scES) in individuals with severe SCI who suffer from chronic hypotension. We tested the hypothesis that CV-scES can increase resting blood pressure and attenuate chronic hypotension in individuals with chronic cervical SCI. Three male research participants with chronic cervical SCI received an implant of a 16-electrode array on the dura (L1-S1 cord segments, T11-L1 vertebrae). Individual specific CV-scES configurations (anode and cathode electrode selection, voltage, frequency and pulse width) were identified to maintain systolic blood pressure within the range of 110-120 mmHg without skeletal muscle activity of the lower extremities as assessed by electromyography. These individuals completed five two hour sessions using CV-scES in an upright, seated position during measurement of blood pressure and heart rate. Noninvasive continuous blood pressure was measured from a finger cuff by plethysmographic technique. For each research participant there were statistically significant increases in mean arterial pressure in response to CV-scES that was maintained within normative ranges. This result was reproducible over the 5 sessions with concomitant decreases or no changes in heart rate using individual specific CV-scES that was modulated with modest amplitude changes throughout the session. Our study shows that stimulating dorsal lumbosacral spinal cord can effectively and safely activate mechanisms to elevate blood pressures to normal from a chronic hypotensive state in humans with severe SCI with individual specific CV-scES.